Association between selected hygiene characteristics and urinary tract infections among children aged 6-12 years in Metro Manila, Philippines - Le Van Hoi
This hospital-based case control study was conducted from September 1998 to January 1999. Twenty-three cases of children with UTI and an equal number of controls were recruited in four tertiary hospitals in Metro Manila, Philippines.The general objective of the study is to determine the relationship betwee selected hygiene characteristics and UTI among children aged 6-12 years. Specifically, the study is designed to examine the relationship between UTI and urination habits, defecation habit, washing habits, bathing habit, history of toilet training, presence of toilet facilities at home or school, and availability of water source for drinking/toilet at home/school.The relationship between UTI and the study variables was determined by using odds ratio, the chi-square test and the Fisher exact test, where appropriate, in simple analysis. Furthermore, exact logistic regression analysis was applied to overcome the problem of small sample size.There was not enough evidence to say that there is a significant relationship between UTI and following study exposures: frequency of urination (OR = 1.42, its 95CI = 0.38-5.41), holding of urination during daytime (X? = 2.04; p = 0.153), permission for urination at school (OR = 0.24, its 95CI = 0.01 - 2.82), bowel movement (OR = 0.83, its 95CI = 0.21-3.28), washing or wiping habit after urination (OR = 1.19, its 95CI = 0.32-4.50) or defecation (exact p = 1.000), manner of washing or wiping in female (OR = 0.20, its 95CI = 0.3-1.39), use of soap for washing (OR = 1.35, its 95CI = 0.23-8.25), bathing habit (X? = 2.69; p = 0.102), history of toilet training (exact p = 1.000), presence of toilet facilities at home (exact p = 0.246) or school (exact p = 1.000), water source for drinking at home (OR = 1.00, its 95CI = 0.26-3.77) or school (exact p = 0.669), water source for toilet at home (OR = 1.42, its 95CI = 0.38-5.41) or school (exact p = 0.121).There was still insufficient evidence to indicate any significant relationship between UTI and holding of urination during daytime (exact p = 0.092), bathing habit (exact p 0.072), presence of toilet facilities at home (exact p 0.104), those which were eligible to consider in bivariate or multivariate exact logistic regression analysis in order to control, one at a time or simultaneously, for each other and selected extraneous variables.Among extraneous variables, there were borderline significant relationships between UTI and group (exact p = 0.044) and enrollment of children (exact p = 0.049) when controlling simultaneously for each other and history of previous UTI, presence of preschooler in household, holding of urination during daytime.This study served as a pilot study of Preventive Nephrology Project (Department of Health, Philippines) in determining selected risk factors of UTI in children. Its results were drawn with limited sample size obtained after a short phase of data collection. A further study should be conducted to obtain more precise and valid results.